If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 209 = (4x + -5)(4x + 3) Reorder the terms: 209 = (-5 + 4x)(4x + 3) Reorder the terms: 209 = (-5 + 4x)(3 + 4x) Multiply (-5 + 4x) * (3 + 4x) 209 = (-5(3 + 4x) + 4x * (3 + 4x)) 209 = ((3 * -5 + 4x * -5) + 4x * (3 + 4x)) 209 = ((-15 + -20x) + 4x * (3 + 4x)) 209 = (-15 + -20x + (3 * 4x + 4x * 4x)) 209 = (-15 + -20x + (12x + 16x2)) Combine like terms: -20x + 12x = -8x 209 = (-15 + -8x + 16x2) Solving 209 = -15 + -8x + 16x2 Solving for variable 'x'. Combine like terms: 209 + 15 = 224 224 + 8x + -16x2 = -15 + -8x + 16x2 + 15 + 8x + -16x2 Reorder the terms: 224 + 8x + -16x2 = -15 + 15 + -8x + 8x + 16x2 + -16x2 Combine like terms: -15 + 15 = 0 224 + 8x + -16x2 = 0 + -8x + 8x + 16x2 + -16x2 224 + 8x + -16x2 = -8x + 8x + 16x2 + -16x2 Combine like terms: -8x + 8x = 0 224 + 8x + -16x2 = 0 + 16x2 + -16x2 224 + 8x + -16x2 = 16x2 + -16x2 Combine like terms: 16x2 + -16x2 = 0 224 + 8x + -16x2 = 0 Factor out the Greatest Common Factor (GCF), '8'. 8(28 + x + -2x2) = 0 Factor a trinomial. 8((4 + -1x)(7 + 2x)) = 0 Ignore the factor 8.Subproblem 1
Set the factor '(4 + -1x)' equal to zero and attempt to solve: Simplifying 4 + -1x = 0 Solving 4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = 0 + -4 -1x = 0 + -4 Combine like terms: 0 + -4 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4Subproblem 2
Set the factor '(7 + 2x)' equal to zero and attempt to solve: Simplifying 7 + 2x = 0 Solving 7 + 2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 2x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 2x = 0 + -7 2x = 0 + -7 Combine like terms: 0 + -7 = -7 2x = -7 Divide each side by '2'. x = -3.5 Simplifying x = -3.5Solution
x = {4, -3.5}
| -3w+16=2(w-7) | | (v-8)(v+8)= | | -5x^3+7x^2-5x-1= | | 3m-16-7m=-68 | | 0.8k+7=-0.7k | | 4x^2+5x+5=0 | | Y=0.10x+12 | | 5t+1= | | x*x-11x+19=-5 | | 8x+7=-7k+1 | | x+84=3 | | 17k+11-3k=214 | | j/5+6=66 | | -3[x-1]+8[x-3]=6x+7-5x | | 4t-5= | | 8x^3+3x^3+5= | | y=-5/4+10 | | 5(2-4X)=-20 | | x/10-6=-7 | | 0.3(1+a)=2.1 | | 12-(10n)=-28 | | 19h-12=197 | | -117+64= | | -112=-7m | | 5-7m+9m=9 | | -3=-6/5(1)+b | | 2x^7=7x | | 4y(y+7)=42 | | 0.3(1+a)=2.1a | | 16/9x=128 | | p(x)=x^5-7x^4-2x^3+78x^2-63x-135 | | 6=(7-2x)(3-2x) |